Aquarium Tests to Study the Detonation Behaviour of a Non-ideal Explosive. - M. Araos (International Society of Explosives Engineers, 2024)
Non-ideal explosives can be characterised by different methods like velocity of detonation measurement, double pipe tests, underwater tests, aquarium tests, etc., to name a few. Both aquarium and velocity of detonation tests were selected to characterise a non-ideal explosive that is based on hydrogen peroxide, fuel, and void sensitisation. The detonation process in an aquarium of this sensitised explosive was captured at 80,000 frames per second using a high-speed camera. The explosive product was detonated using 51mm (2inches) diameter acrylic pipe charges. The product was detonated at different densities in an aquarium (cube box containing water). An aquarium provides a homogenous confinement for the detonation of explosives and more importantly, allows observing the shock wave as it changes the refraction index of water. The analysis of the video footage allowed the calculation of the velocity of detonation, pressure, gas rate release, and how the shock wave's shape in water changes with densities. It is suggested that the calculation of the rate of gas release could be related to the bubble data obtained from underwater tests.